The Role of Technology Acceptance Model in Explaining University Academics’ Acceptance and Behavioural Intention to Use Technology in Education - Ibrahim, T A (KnE Social Sciences, 2018)
As the use of modern technology in education continues to grow at all levels of education, and academics are believe to be among the major actors in educational transformation, there is an increasing need to better understand the acceptance and behavioural intention of University academics to use technology in education because few studies were conducted to that effect. Hence, the purpose of this research was to find the level of technology acceptance among university academics using TAM as theoretical model. A survey was used using a sample of 355 academics from Nigerian universities. Regression analysis and Structural Equation Modelling (SEM) were used for the data analyses and model fit using SPSS and AMOS softwares. The result proved TAM to be a good theoretical tool to understand users’ acceptance of technology. The findings revealed that the variances in Self Efficacy (SE), Social Influence (SI), System Accessibility (SA), Perceived Usefulness (PU) and Perceived Ease of Use (PEOU) really contribute to change in Behavioural Intention (BI) to use technology. However, the study also revealed that there are significant relationships between BI and SE, SA, and PU, but insignificant relationship was found between BI and the other two constructs i.e PEOU and SI. Since technology is not easy to use, and there is less social influence to help them use the system adequately, therefore, perhaps there is need for management to organize more trainings, seminars and workshops with regards to the use of the technology for the academics. Keywords: Analysis of Moment Structure (AMOS), Behavioural Intention, Structural Equation Modelling (SEM), Technology Acceptance Model (TAM).Introduction